Analisis Pengukuran Kinerja Koperasi Dengan Menggunakan Metode Analitycal Hierarchy Process Pada Koperasi San Dominggo Hokeng - Paskalia Irvanti Ema Lewar; Wilhelmina Mitan; Pipiet Niken Aurelia (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to measure the performance of the San Dominggo Hokeng cooperative using the Analytical Hierarchy Process method which includes financial and non-financial dimensions. The type of research used in this research is descriptive quantitative research. Data collection techniques using observation techniques, interviews, documentation, and literature study. Sources of data from this study are primary data and secondary data. The data analysis technique in this study is to use the formula and analysis of the Analytical Hierarchy Process. The results of this study indicate that the performance of the San Dominggo Cooperative in the financial dimension has the highest weighted result with a value of 0.6226. Meanwhile, the non-financial dimension has a weight with a value of 0.3774. The results of this study indicate that the performance of the San Dominggo cooperative is in good condition. This happens because cooperatives have paid attention to and implemented indicators from financial and non-financial dimensions. Even so, there are several indicators that need to be considered because of decreased performance to maintain the performance of the San Dominggo cooperative in the future.